Pregnancy-Associated Plasma Protein A2 in Hemodialysis Patients: Significance for Prognosis - Marta Kalousová; Sylvie Dusilová-Sulková; Aleš A. Kuběna; Oskar Zakiyanov; Kateřina Levová; Markéta Bocková; Erika Gedeonová; Xue Chadtová Song; Maria Laura Ermini; Tomáš Špringer; Jiří Homola; Vladimír Tesař; et al. (Karger Publishers, 2017)
Background: Pregnancy-associated plasma protein A (PAPP-A) is associated with adverse outcome of long-term hemodialysis patients (HD). The aim of the study was to test whether its homolog pregnancy-associated plasma protein A2 (PAPP-A2) can be detected in serum of HD patients and to define its significance. Methods: The studied group consisted of 102 long-term HD patients and 25 healthy controls. HD patients were prospectively followed up for five years (2009-2014). PAPP-A2 was measured by surface plasmon resonance biosensor, PAPP-A by time resolved amplified cryptate emission. Results: PAPP-A2, similarly as PAPP-A, was significantly increased in HD patients (median (interquartile range)) PAPP-A2: 6.2 (2.6-10.8) ng/mL, vs. 3.0 (0.7-5.9) ng/mL, p=0.006; PAPP-A: 18.9 (14.3-23.4) mIU/L, vs. 9.5 (8.4-10.5) mIU/L, p<0.001). In HD patients, PAPP-A2 correlated weakly but significantly with PAPP-A (τ=0.193, p=0.004). Unlike PAPP-A, PAPP-A2 was not significant for prognosis of HD patients when tested alone. There was a significant interaction between PAPP-A and PAPP-A2 on the mortality due to infection of HD patients (p=0.008). If PAPP-A was below median, mortality due to infection was significantly higher for patients with PAPP-A2 values above median than for patients with low PAPP-A2 levels (p=0.011). Conclusion: PAPP-A2 is increased in HD patients and interacts with PAPP-A on patients´ prognosis.